Dynamism of Ribosomal Protein RPL28 as Biomarker for Monitoring Epigenetic-initiated-breast-cancer Therapy - CAPO-CHICHI, D. CALLINICE (My University, 2019)
Background: Many oncology biomarkers were reported for breast cancer diagnosis and targeted therapy. Most biomarkers were hormonal receptors, but few studies integrated GATA transcription factors, nuclear envelop protein lamin A and ribosomal proteins, all of which were disrupted in cancer to facilitate cell proliferation, migration and metastasis. The overexpression of GATA6 in breast cancer cells is involved in epithelial-mesenchymal transition (EMT) while the overexpression of ribosomal large subunit (60S) protein RPL28 is involved in protein synthesis and cell proliferation. The objective of this study is to investigate in breast cancer cell line MCF7 the expression profile of GATA6 and RPL28 as biomarkers to evaluate the efficiency of breast cancer therapy with histone deacetylase inhibitor Suberoyl-Bis-Hydroxamic Acid (SBHA) in case that epigenetic modifications influence protein expression. Methods: Immuno-blot was used to assess GATA6 and RPL28 expression profile in MCF7 cell lysate before and after treatment with SBHA for 12h. GATA6 and RPL28 were also assessed in presence and absence of nuclear envelop protein lamin A in MCF7 stably transfected with exogenous wild type lamin A conjugated to red fluorescent protein (LA-RFP). Results: Our principal findings were that GATA6 and RPL28 were overexpressed in MCF7 lacking lamin A. GATA6 expression is higher in MCF7 control lacking lamin A. Exogenous transfection of LA-RFP in MCF7 was enough to reduce GATA6 and RPL28 at a background level like the one obtained with SBHA treatment. Conclusions: The significance of our study is that breast cancer therapy can be achieved with histone deacetylase inhibitor in case that epigenetic modifications underlie and initiate cancer mechanisms. The dynamism of biomarkers GATA6 and RPL28 can be used as bio-indicators to evaluate anti-cancer drug effectiveness.
Keywords: breast cancer; epigenetic modifications; GATA6 transcription factor; ribosomal protein RPL28; Histone deacetylase inhibitor; Suberoyl-Bis-Hydroxamic Acid; lamin A